THE IMPACT OF ACCOUNTING DIGITALIZATION ON MSMEs’ FINANCIAL PERFORMANCE: A RESOURCE-BASED VIEW PERSPECTIVE IN THE CONTEXT OF FINANCIAL LITERACY AND GREEN FINANCE - Saraswati, Esti; Yuliarti, Lusi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study investigates the impact of accounting digitalisation, financial literacy, and access to green finance on the financial performance of micro, small, and medium enterprises (MSMEs) in Patikraja District, Central Java, Indonesia. Method: Using a quantitative explanatory design, data were collected from 150 valid questionnaires via purposive sampling, with the sample size determined using Slovin’s formula. Multiple linear regression analysis with SPSS version 25 was employed, supported by validity, reliability, and classical assumption tests. The results show that all three independent variables significantly influence MSME financial performance. Among them, financial literacy exerts the strongest positive effect, followed by accounting digitalization and access to green finance. Results: These findings demonstrate that financial knowledge and digital accounting adoption are essential for profitability, efficiency, and resilience, while sustainable financing further supports eco-friendly practices and long-term stability. This study contributes to the Resource-Based View (RBV) literature by integrating financial, technological, and sustainability perspectives. It offers practical implications for policymakers to strengthen literacy programs, expand access to digital tools, and improve MSME access to green finance. Keywords: Accounting Digitalisation, Financial Literacy, Financial Performance, Green Finance, MSMEs